Pequod or "the black tragedy of the melancholy ship" : A Reading of Herman Melville’s Moby-Dick - Lemos, Márcia (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
.